THE Boards of judicial administration counselors:: Analysis of legal framework and reform proposals. Particular reference as useful tool for criteria unification (Acta Judicial Journal, 2018)
This article deals with the main aspects of the Boards juridical regime that can held by the Judicial Administration Counselor, regulated in the article 26 of the Organic Regulation, exposing the different kinds of Boards they can convene, form of constitution and operation, as well as their possible content. But, above all, it is intended to formulate a series of lege ferenda proposals in order to relaunch and streng this body's ordination tool so that Boards become an everyday and truly useful tool for the work of the Justice Administration Counselor. It is essential to specify with greater precision, its possible content and the effects derived from the agreements adopte, among other aspects. Reflecting at the same time about the special utility that these Boards may have to try to unify criteria in the procedural field and about its cohesive effect in small judicial districts.
Keywords: Boards, Judicial Administration Counselor, legal regime, classes, convocation, operation, agreements, effects, unification of criteria